Valdosta High School Scrapbook 39, 1989-1990 - Valdosta High School (My University, 1989)
This item is a scrapbook collection with newspapers articles and photographs regarding Valdosta High School. This item focuses primarily on the 1989 football season culminating in a state championship title. Other sports like sports like Basketball, Softball, Baseball, and wrestling are mentioned.
This item has 1 PDF file with 196 Pages and a title page with 99 JPG files
Keywords: Newspapers; Photographs; Scrapbooks; Lowndes County (Ga.); American Football; Softball; Marching bands; Basketball